A New Version of the Impairment and Functioning Inventory for Patients With Chronic Pain (IFI‐R). Issue 5 (18th December 2014) - Ramírez‐Maestre, Carmen; Esteve, Rosa
Abstract: Background: Few instruments are available that have adequate psychometric properties for assessing daily functioning in patients with musculoskeletal pain. In addition, none of these instruments assesses the perceived decrease in levels of daily activities after the onset of pain. Objective: To review the psychometric qualities of the Impairment and Functioning Inventory (IFI) for patients with chronic pain. Design: Cross‐sectional study. Setting: Four public primary care centers and a public pain clinic. Patients: A total of 483 patients with back pain who were treated at primary care centers and 137 patients with various pain conditions who were treated at a pain clinic. Methods: To analyze factorial validity, a confirmatory factor analysis was performed via structural equation modeling. To measure internal consistency, Cronbach's α coefficients were calculated. To assess convergent validity, Pearson correlation coefficients were computed between the 2 scales of the IFI and the measures of the Roland Morris Questionnaire. Criterion validity and generalizability were analyzed by regression analysis via structural equation modeling using the LISREL 8.30 software package. Main Outcome Measures: The IFI for patients with chronic pain. Results: A revised version of the IFI (IFI‐R) is presented that consists of 30 items with 2 related subscales: Daily Functioning and Impairment (perceived current level of functioning compared with the level of functioning before pain onset). Both subscales were significantly correlated with disability. Depression, pain intensity, and pain anxiety had a negative association with functioning and a positive association with impairment. On the other hand, pain catastrophizing had a negative association with functioning and pain hypervigilance had a positive association with impairment due to pain. Conclusions: The IFI‐R appears to be a valid and reliable measurement tool for the assessment of perceived daily functioning and impairment in people with chronic pain.